Sağlık Kuruluşlarında Kişilerarası İletişim - Karadağ Alçı, Şule (Academician Publishing Book DOI Portal, 2023)
Bu kitap, sağlık kuruluşlarında kişilerarası iletişimin önemine odaklanmaktadır. İletişim, insanların sosyal yaşamında vazgeçilmez bir unsurdur ve sağlıklı bir yaşamın temelini oluşturur. Sağlık, bireyin günlük yaşamından iş hayatına kadar her alanda etkili olan hassas bir konudur. Son yıllarda sağlık okuryazarlığının önemi artmış ve bireyler sağlıkları konusunda daha bilinçli hale gelmiştir. Bu nedenle, sağlık hizmeti sunucularının hasta ve hasta yakınlarına yaklaşımları büyük önem taşımaktadır. İyi iletişim becerileri ve yaklaşımlar, hastaların kendilerini ifade etmelerine, tanı ve tedavi sürecinin iş birliği içinde yürütülmesine katkı sağlar. Ayrıca, sağlık kuruluşlarının iç iletişimi ve çalışanların iletişim becerilerinin geliştirilmesi de önemlidir. Bu kitap, sağlık kuruluşlarında kişilerarası iletişim engelleri ve çözüm yolları konusunda öneriler sunmaktadır. This book focuses on the importance of interpersonal communication in healthcare institutions. Communication is an essential element in people’s social lives and forms the foundation of a healthy life. Health is a sensitive issue that affects individuals in every aspect of their daily lives, from personal to professional. In recent years, the importance of health literacy has increased, and individuals have become more conscious about their health. Therefore, the approach of healthcare providers towards patients and their families is of great importance. Good communication skills and approaches contribute to patients expressing themselves and the collaborative management of diagnosis and treatment processes. Additionally, improving internal communication within healthcare institutions and enhancing employees’ communication skills are also important. This book offers suggestions on overcoming barriers to interpersonal communication in healthcare institutions and provides solutions.